Design and analysis wavelength division multiplexing (WDM) system with erbium-doped fiber amplifier (EDFA) - Engku Azizul Hilmi Engku Umar
This final year project is about to develop a point-to-point WDM system with EDFA to see the performance of the WDM system, focusing on each channels output.